New and noteworthy species of Begonia (Begoniaceae) from Vietnam and Laos - Averyanov, Leonid V.; Nuraliev, Maxim S.; Konstantinov, Eugene L.; Maisak, Tatiana V.; Kopylov-Guskov, Yury O.; Lyskov, Dmitry F.; Quang, Bui Hong; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Nguyen, Khang Sinh; Shui, Yu-Min (Phytotaxa, 2021)
The paper provides additions to the known diversity of Begonia in Vietnam and Laos. One species new to science from Lao PDR (B. vivipara) and three new species from Vietnam (B. aspersa, B. gracilifolia, B. maculifolia) are described. Three species (B. rotundilimba, B. versicolor, B. wenshanensis) are reported as new records for the flora of Vietnam. For each species, the information on ecology, phenology, estimated conservation status and distribution is presented, as well as the relevant taxonomic notes and analytical photographic illustrations.